Efek Penempatan dan Motivasi Kerja Terhadap Kepuasan dan Pengembangan Karir Pegawai - Ridwan Saleh, Harmelia; Amang, Baso; Selong, Abbas (AkMen JURNAL ILMIAH, 2025)
This study aims to examine the Influence of Placement and Work Motivation on Employee Satisfaction and Career Development at PT PLN (Persero) UIT JBTB. The population in this study is 1,116 employees of PT PLN (Persero) UIT JBTB in 2025. The research sample used the AccidentaI method through a questionnaire distributed to respondents and processed by researchers as many as 97 respondents. The data analysis technique was carried out by descriptive statistical analysis and PLS (Partial Least Square). The results of the hypothesis test show that job placement has a positive and significant effect on the job satisfaction of PLN UIT JBTB employees, Job motivation has no effect on the job satisfaction of PLN UIT JBTB employees, Job placement has no effect on the career development of PLN UIT JBTB employees, Work motivation has a positive and significant effect on the career development of PLN UIT JBTB employees, Job satisfaction does not have a positive and significant effect on the career development of PLN employees UIT JBTB, Job satisfaction does not function as a mediating variable that bridges the relationship between job placement and career development of PLN UIT JBTB employees, job satisfaction does not play a mediating variable in the relationship between work motivation and career development of PLN UIT JBTB employees. This proves that the career development programs that have been carried out by the company have not had a major impact on increasing employee satisfaction and motivation at PLN UIT JBTB.